Two new flavonoids and anticancer activity of Hymenosporum flavum: in vitro and molecular docking studies - Rehab Fikry Taher; Ahmed A. Al-Karmalawy; Ahmed I. Abd El Maksoud; Hany Khalil; Amr Hassan; Ezzel-Din; Walaa El-Kashak (Shahrekord University of Medical Sciences, 2021)
Introduction: Hymenosporum flavum (Hook.) F. Muell. is the sole species within the genus Hymenosporum is known for its antimicrobial activity. The current study aims to examine the prospective activity of H. flavum as a safe supporter of sorafenib (as a reference standard) against hepatocellular carcinoma (HCC). Methods: Isolation and identification of compounds were made by chromatographic and spectroscopic methods. A fingerprint for the plant extract was done using HPLC-MS/MS spectrometric analysis. The total plant extract was examined in vitro for HCC activity. The isolated flavonoids were examined for their cytotoxic activities using molecular docking studies against both RAF-1 and ERK-2, and the promising compounds were further examined in vitro using quantitative reverse transcription-polymerase chain reaction (qRT-PCR). Results: Two new flavonols were isolated from the leaf extract of H. flavum (Hook.) F. Muell., quercetin-3-O-(glucopyranosyl 1→2 ribopyranoside) (1) and kaempferol-3-O-(glucopyranosyl 1→2 ribopyranoside) (2), accompanying other six known flavonoids (3-8), and identified via spectroscopic analysis. Moreover, HPLC- PDA/MS/MS spectrometric analysis revealed the presence of seventy phenolic metabolites. The cytotoxic activity of the plant extract confirmed its potential action on HepG2 cells indicated by the production level of lactate dehydrogenase (LDH) upon treatment compared with the normal cells. The isolated flavonoids were examined for their cytotoxic activity using molecular docking studies against both RAF-1 and ERK-2 as proposed mechanisms of their anticancer activities. Furthermore, compounds 1 and 3, which showed the best in silico results, were further examined in vitro using qRT-PCR. They exhibited promising inhibitory activities against both RAF-1 and ERK-2 gene expression. Moreover, they showed promising cytotoxic activities indicated by the MTT assay. Also, both of them improved the efficiency of sorafenib in targeting both RAF-1 and ERK-2 pathways suggesting synergistic combinations. Conclusion: Our findings showed the potential cytotoxic activity of H. flavum extract on HepG2 cells. Some isolated compounds (1 & 3) exhibited promising inhibitory activities against both RAF-1 and ERK-2 gene expression giving a lead future study for these compounds to be used in pharmaceutical preparations either alone or in combination with sorafenib.